2023
DOI: 10.1186/s12933-023-01800-z
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effect of GLP-1 receptor agonists on cardiovascular benefits: a real-world study

Abstract: Background Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have shown cardiovascular benefits in cardiovascular outcome trials in type 2 diabetes mellitus. However, the most convincing evidence was obtained in subjects with established cardiovascular (CV) disease. We analyzed the determinants of GLP-1 RA-mediated CV protection in a real-world population of persons with type 2 diabetes with and without a history of CV events with long-term follow-up. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“… 49 , 50 This was supported by an observational study, albeit in people living with diabetes, that reported an increased risk of CVD events in those who withdrew GLP-1 RAs. 51 …”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 This was supported by an observational study, albeit in people living with diabetes, that reported an increased risk of CVD events in those who withdrew GLP-1 RAs. 51 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to losing the cardiorenal protection benefits, individuals who discontinue GLP-1 RA medications typically gain back much of the weight they had lost during therapy [ 55 ]. In a retrospective cohort study of adults with T2D, investigators assessed changes in cardiovascular risk and other outcomes in 395 individuals with no history of CVD (primary prevention group) and 155 individuals with a known history of CVD (secondary prevention) [ 55 ]. In the primary prevention arm of the trial ( n = 395), 40.25% of patients discontinued therapy after mean of 3.2 years.…”
Section: Strengths and Limitations Of Glp-1 Ra Therapymentioning
confidence: 99%
“…At year 4, weight loss was significantly greater among patients who continued therapy than among those who discontinued therapy (− 4.14 vs. − 1.19 kg; respectively; p < 0.001), and even greater differences were observed in the secondary prevention group (− 4.46 vs. − 0.75 kg, respectively; p = 0.006). The investigators reported that discontinuation of therapy was independently associated with a significant increase in the risk of developing a major adverse cardiovascular event (MACE) [ 55 ].…”
Section: Strengths and Limitations Of Glp-1 Ra Therapymentioning
confidence: 99%
“…However, although GLP-Ras have actually been shown to improve cardiovascular risk factors such as body weight, blood pressure, LDL cholesterol and triglycerides, and glycemic control, they have been shown to reduce all-cause mortality in patients with type 2 diabetes at high risk of cardiovascular events, but have not reduced cardiovascular mortality, non-fatal myocardial infarction, non-fatal stroke and hospitalizations for HF ( 71 , 72 ). Another recent meta-analysis carried out on 54,092 pts from 7 randomized controlled trials on the use of GLP-1 Ras in subjects with type 2 diabetes, of whom 16% also had a history of HF, demonstrated that these drugs appear to protect the diabetic population from the development of HF, but, in subjects with pre-existing HF, they do not reduce the onset of episodes of HF exacerbation with consequent hospitalization, nor mortality ( 73 ).…”
Section: Tratment Of Ir/hyperinsmentioning
confidence: 99%